Concussion severity and functional outcome using biomarkers in children and youth involved in organized sports, recreational activities and non-sport related incidents. (3rd July 2022) - Papa, Linda; Rosenthal, Kimberly; Cook, Laura; Caire, Michael; Thundiyil, Josef G.; Ladde, Jay G.; Garfinkel, Alec; Braga, Carolina F.; Tan, Ciara N.; Ameli, Neema J.; Lopez, Marco A.; Haeussler, Crystal A.; et al.
ABSTRACT: This prospective multicenter study evaluated differences in concussion severity and functional outcome using glial and neuronal biomarkers glial Fibrillary Acidic (GFAP) and Ubiquitin C-terminal Hydrolase (UCH-L1) in children and youth involved in non-sport related trauma, organized sports, and recreational activities. Children and youth presenting to three Level 1 trauma centersfollowing blunt head trauma with a GCS 15 with a verified diagnosis of a concussion were enrolled within 6 hours of injury. Traumatic intracranial lesions on CT scan and functional outcome within 3 months of injury were evaluated. 131 children and youth with concussion were enrolled, 81 in the no sports group, 22 in the organized sports group and 28 in the recreational activities group. Median GFAP levels were 0.18, 0.07, and 0.39 ng/mL in the respective groups (p = 0.014). Median UCH-L1 levels were 0.18, 0.27, and 0.32 ng/mL respectively (p = 0.025). A CT scan of the head was performed in 110 (84%) patients. CT was positive in 5 (7%), 4 (27%), and 5 (20%) patients, respectively. The AUC for GFAP for detecting +CT was 0.84 (95%CI 0.75–0.93) and for UCH-L1 was 0.82 (95%CI 0.71–0.94). In those without CT lesions, elevations in UCH-L1 were significantly associated with unfavorable 3-month outcome. Concussions in the 3 groups were of similar severity and functional outcome. GFAP and UCH-L1 were both associated with severity of concussion and intracranial lesions, with the most elevated concentrations in recreational activities .